Apa de Balbino – Cascavel / CE: subsídios para o ordenamento territorial - Albuquerque, Bruna Maria Rodrigues de Freitas (2012)
This study was developed in the Environmental Protected Area (EPA) of Balbino, Unit of Sustainable Conservation, which has a geographical area of 250 ha, located at municipality of Cascavel coast It was contextualized all the conditions of the town and the context was characterized socio environmental of the Balbinos’s community Thus, based on the dynamics analysis of EPA, and the aspects that interfere in the landscapes ,some subsidizes have been proposed that enable the land management according to the economics and natural resources available in that area, presenting the environmental zoning as the main subsidize. This study was based on Geosystemic Theory making possible an integrated analysis of the environmental elements, biological and social in that area. To collect data, information contribution was made by the fieldwork, interviews with residents and local leaderships and workshops for children and teenagers. From the survey, a socio environmental diagnostic was prepared including the land use and occupation of the landscapes, with problems and such as problems and potentialities. Thus, some proposals were made to social environmental context to EPA of Balbino. In this way ,intends to understand the contributions of this survey to management of EPA and realization of zoning environmental through the environmental public organizations.